Nuclear Industry in the Eyes of Russians: Trust and Its Determinants - I. A. Ankudinov; R. N. Abramov (Социология власти)
Over the past decade, there has been growing positive interest in nuclear technologies as a sustainable source of clean electricity for the West and as a factor of industrial and social growth in Southeast Asia. Both developed and developing countries face the need to meet growing energy consumption needs, which is especially difficult in the context of gas market shocks and large-scale green transition plans. The social dimension of this problem, especially in the reactor-building countries, often remains “behind the scenes”. Russia is one of the oldest countries with a powerful nuclear plant system, but even here the public’s attitude to the “peaceful atom” is ambiguous. Socio-political radiophobia has accompanied the development of the nuclear industry since at least the Chernobyl accident, and sociological publications that would topicalize the mood of Russian citizens, their level of anxiety and trust in nuclear energy are still sparse. The article examines Russians’ perception of nuclear technology in general and specifically regarding the “Development of Engineering, Technologies and Scientific Research in the Use of Nuclear Energy in the Russian Federation” (DETSR) program and the Rosatom state corporation’s activities. Based on two waves of representative surveys conducted in April-May 2023-2024, we assess the factors that contribute to the formation of trust in the industry. Using factor regression analysis, structural equations, and nonparametric tests, we outline a demographic profile of a Russian “nuclear optimist” — such optimism being typical primarily for the well-off segments of the population. A key role in the interpretation is given to the awareness factor, the increase of which (in the long term) should smooth out the inequality in support for the industry. The issue of (dis)trust in the state and its impact on this support is also discussed.